Cinnamaldehyde Attenuates the Expression of IBA1 and GFAP to Inhibit Glial Cell Activation and Inflammation in the MPTP-Induced Acute Parkinson’s Disease Model - Panpan Jiao; Yingfeng An; Suhui Wu; Hanbing Li; Genlin Li (Parkinson's Disease)
Cinnamaldehyde (CA), the primary bioactive compound in cinnamon (Cinnamomum cassia Presl, Lauraceae, Cinnamomum), holds potential therapeutic benefits for Parkinson’s disease (PD). To scrutinize the impact and mechanisms of CA on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD, male C57BL/6 mice were randomly allocated to CA (150, 300, and 600 mg/kg), model, Madopar, and control group (n = 12). The Open Field, Pole-jump, and Rotarod experiments assessed exercise capacity and anxiety levels. HPLC evaluated the levels of neurotransmitters. Immunohistochemistry was utilized to detect the expression of TH and GFAP. WB and RT-qPCR determine the expression levels of apoptosis-related genes and proteins in the substantia nigra and striatum. The findings revealed that CA not only enhanced motor abilities and reduced anxiety but also elevated the levels of TH, DOPAC, DA, 5-HIAA, HVA, and 5-HT in the substantia nigra and striatum. Moreover, it protected DA neurons and downregulated the expression of Bax, Casp3, and Bax/Bcl-2 mRNA and proteins, while increasing the expression of Bcl-2 mRNA compared to the model group. Furthermore, CA was observed to inhibit glial cell activation, leading to reduced levels of GFAP and IBA1 in the substantia nigra and striatum. This resulted in decreased expression of inflammatory factors such as iNOS and NF-κBp65 proteins in these regions, consequently mitigating neuroinflammation. These results suggest that CA exerts a neuroprotective effect in acute PD model mice by suppressing glial cell activation, modulating the expression of apoptotic genes, and alleviating neuroinflammation and apoptosis induced by MPTP.